Combining instruction and immersion to improve pronunciation: The case of Chinese students learning bahasa Indonesia - Suroso Suroso; Emi Nursanti; Nan Wang (Faculty of Languages, Arts, and Culture Universitas Negeri Yogyakarta, 2023)
In pronunciation classes, most teachers over-emphasize the accuracy part and ignore the fluency aspects (Elliot, 1995; Yoshida, 2016). To enhance both accuracy and fluency for Chinese students’ pronunciation in Bahasa Indonesia (BI), this study investigates the effects of combining instruction and immersion. This was classroom action research conducted for one semester at Qujing Normal University (QJNU), Yunnan Sheng, China. Audiolingual Method (ALM) with drilling technique was the instruction procedure while the outdoor project was the technique in the immersion. The research subjects were nine first-semester students in the Indonesian Language Department of QJNU. Their score improvements from the pre- to post-assessments indicate that combining these two methods is effective in enhancing students’ pronunciation in BI. The instruction conducted through explicit phonetic teaching and drilling is appropriate for habituating them with accurate pronunciation. Meanwhile, the fun and enjoyable immersion in contextual settings boosts their fluency and gives them opportunities to explore and practice using the words they have learned in real contexts. Along with pronunciation improvement, enhancement in students’ learning attitude and engagement in the learning activities are the other benefits that may contribute to their success in gaining full fluency in the second language. Keywords: drilling, immersion, pronunciation, Chinese students, BIPA